Evaluation of Various Traits of some Bean (Phaseolus vulgaris L.) Genotypes in Ilam Climatic Conditions - Fatemeh Kamari; Zahra Tahmasebi (پژوهش‌های حبوبات ایران, 2025)
Introduction Common bean (Phaseolus vulgaris L.) is a vital legume, rich in protein and nutrients, that is significantly impacted by the two-spotted spider mite (Tetranychus urticae), leading to substantial economic losses in agricultural fields. Given the limitations of chemical control and its environmental consequences, the identification and utilization of resistant cultivars represent a sustainable approach to pest management. Various studies have demonstrated that certain bean genotypes possess morphological and physiological characteristics that effectively reduce mite populations. To date, a comprehensive assessment of bean genotype resistance to T. urticae under the climatic conditions of Ilam province has not been conducted. This research aims to evaluate the resistance of 25 bean genotypes to this pest under field conditions in Ilam, with the goal of identifying resistant varieties for integration into breeding programs and sustainable agricultural practices. Materials and MethodsThis research was conducted during the 2021-2022 growing season at the research farm of Ilam University to identify resistant and high-yielding bean varieties against T. urticae. Twenty-five bean genotypes (10 cultivars and 15 lines), including the susceptible cultivar "Akhtar," were obtained from the gene bank of Tehran University and planted in a randomized complete block design (RCBD) with three replications. Following spring plowing, planting was carried out in June 2021, and irrigation was performed using the flood irrigation method every 3 to 4 days. Symptoms of infestation appeared during the flowering stage, and the extent of damage to the leaves was assessed using a five-point scale (0 = no infestation, 4 = severe damage). Phenological traits (days to flowering and podding) and morphological traits (plant height, pod length and width, number of seeds and pods) were measured, and the yield of each genotype was calculated based on the total weight of the seeds. Results and Discussion The results of this research indicated that there was considerable genetic diversity for all of the traits that were investigated. Based on the results of analysis of variance, the results of analysis of variance showed that there was a significant difference between genotypes in terms of all traits at the 1% level. Genotypes "Goli" and "D81083" were identified as the most resistant and had the highest yield (101.5 g per plant), while genotype "288" showed the most susceptibility and the lowest yield (0.42 g per plant). Cultivar "Goli" had the highest number of pods (37.7 per plant), and cultivar "323" had the lowest number of pods (2.67 per plant). Additionally, cultivar "Goli" had the highest number of seeds per pod (5.1), and cultivar "Local Azna" had the lowest number of seeds per pod (1.8). In terms of plant height, cultivar "1090" had the tallest plants at 122.7 cm, and cultivar "Khomein" had the shortest plants at 36.1 cm. The greatest pod length (10.6 cm) was observed in cultivar "Derakhshan," and the shortest length (1.6 cm) in cultivar "79EMERSON." A significant negative correlation between mite damage and yield (r = -0.78) indicated that increased damage leads to lower yield. Cluster analysis divided the genotypes into four groups, with genotypes "Goli" and "D81083" in the resistant group and genotypes "1090" and "288" in the susceptible group. These results confirm that the use of resistant genotypes can help reduce pest damage and increase yield. Correlation analysis showed that the level of pest damage has a negative and significant correlation with yield and its components (r=-0.78). Cluster analysis divided genotypes into four groups: resistant, semi-resistant, semi-susceptible, and susceptible. ConclusionsHigh genetic diversity was observed in the studied cultivars and lines; cultivar 288 was the most sensitive, and cultivars D81083 and Goli were the most resistant and high yielding. There was a positive correlation between the number of pods and seeds per plant with seed yield. Cluster analysis divided the cultivars into four groups, with the fourth group including the D81083 and Goli cultivars having the best performance and resistance.